Sex and age differences in the COVID-19 mortality in East Jakarta, Indonesia: Analysis of COVID-19 surveillance system - Sumiati Sumiati; Nur Aini; Tika Dwi Tama (AOSIS, 2022)
Demographic factors have been reported to worsen COVID-19 outcomes. However, there is limited evidence about the different effects of sex and age on COVID-19 death in East Jakarta, Indonesia. This study examined the association between sex and age with COVID-19 mortality. Using COVID- 19 surveillance data of East Jakarta from March 2020 to December 2021, we calculated COVID-19 mortality and examined the risk of COVID-19 death by sex and age. The risk of COVID-19 death associated with sex and age was examined by using Multiple Logistic Regression. A total of 202.412 cases were analyzed and 1.9% of them died. The elderly had a 41.88-folds increased risk of COVID-19 mortality than younger patients (45 years) (aOR 41.88; 95% CI 37.49-46.77; p-value 0.0001). Male had a higher risk of COVID-19 death compared to female (aOR 1.27; 95% CI 1.19-1.35; pvalue 0.0001). Age and sex had a significant association with COVID-19 mortality. Adequate management of COVID-19 cases, particularly in the elderly and male patients, may reduce the severity of COVID-19 or even mortality.